Ummi Method Training at TPQ Al-Azhar Dusun Gapuk as an Effort to Improve Reading Fluency Al-Qur’an - M. Zainuddin Alanshari; Siti Suwaibatul Aslamiyah; Sintya Tri Cahyani (Shof Journal of Social Impact, 2024)
This research is entitled Ummi method training as an effort to increase fluency in reading the Al-Qur'an using qualitative research and a descriptive approach. The aims of this research are: (1) to find out how to apply the Ummi method at TPQ Al-Azhar Dusun Gapuk (2) to find out how to improve fluency in reading the Al-Qur'an at TPQ Al-Azhar Dusun Gapuk (3) to determine the supporting and inhibiting factors for implementing the Ummi method in increasing fluency in reading the Al-Qur'an at TPQ Al-Azhar Dusun Gapuk. The result of this research is the application of the Ummi method at TPQ Al-Azhar Dusun Gapuk through 7 stages, namely opening, apperception, concept planting, concept understanding, skills/training, evaluation and closing. Efforts to increase fluency in reading the Al-Qur'an at TPQ Al-Azhar include increasing understanding and practicing learning the science of recitation and makharijul huruf.